Urgensi Meng-Upgrade Niat sebagai Upaya dalam Memperkuat Keimanan di Tengah Darurat Moralitas: Studi Takhrij dan Syarah Hadis - Fadly Alanka (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about intention. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about intention in Bukhari's narration No.1. The results and discussion of this study indicate that the status of the hadith is of sahih quality that meets the qualifications of maqbul and ma'mul bih for the practice of Islam. This study concludes that the Hadith narrated by Bukhari No.1 is relevant to be used as an effort to add insight for all Muslims in the midst of a morality emergency.